Enegrecendo o whatsapp: uma análise sobre a (re)apropriação da identidade cultural do grupo Juventude Negra Kalunga pelo uso do aplicativo - Silva, Luizete Vicente da (2018)
This research project aims to analyze the sociopolitical production of black digital activism by observing the use of the Whatsapp application by the group "Black Youth Kalunga", a group formed by young blacks that aims to discuss racial relations, with emphasis on the practice of youth empowerment and the identity of youth from its inception in this application. It is intended to observe how the group interacts in this cyberspace and the unfolding that this virtual environment develops in face-to-face relationships and in the construction of spaces of discussion for the exercise of black youth citizenship.